2012
DOI: 10.1097/ajp.0b013e318227cc4f
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-controlled Trial of Acetaminophen Extended Release for Treatment of Post-marathon Muscle Soreness

Abstract: Acetaminophen ER 1300 mg, a nonprescription drug, was an effective treatment for post-race muscle soreness on the day of the marathon. In addition, acetaminophen ER provided benefit for interference with sleep and overall satisfaction with treatment, and was generally well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We know of only one study to use such a strategy; they tested the efficacy of acetaminophen on muscle soreness post marathon running and successfully recruited over 600 participants [83].…”
Section: Recruiting People With Muscle Painmentioning
confidence: 99%
“…We know of only one study to use such a strategy; they tested the efficacy of acetaminophen on muscle soreness post marathon running and successfully recruited over 600 participants [83].…”
Section: Recruiting People With Muscle Painmentioning
confidence: 99%
“…In addition to the beneficial effect of acetaminophen on relieving muscle soreness and pain (Prior et al, 2011), recent studies have suggested that acetaminophen can improve aged skeletal muscle structure and function (sarcopenia). Wu et al (2009b) firstly reported that chronic acetaminophen treatment at 30 mg/kg body weight is able to decrease the amount of aging-associated myocyte apoptosis and increase myocyte size (muscle fiber cross sectional area), with this latter effect occurring most likely associated with an increase in myosin and actin expression in aged muscle.…”
Section: Chronic Acetaminophen Ingestion Can Improve Blood Glucose Comentioning
confidence: 99%
“…The pharmacokinetics of paracetamol do not appear to be modified by exercise (ie, plasma concentration, clearance, and half‐life) and do not change during exercise compared with rest [25]. Paracetamol intake has not been associated with serious adverse events among most users [11], although some frequently reported mild‐to‐moderate side effects of short‐term administration within the therapeutic dose (maximum of 3 g daily) include nausea, vomiting, diarrhea, and abdominal pain. Liver failure has been reported after an overdose of paracetamol (>10 g) [26].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in contrast to the postexercise use of analgesics to accelerate recovery, there is potential for their prophylactic use as a potential performance‐enhancing intervention. In comparison with what is known about the use of analgesics for treating sporting injury [10,11], much less is known about their effects on exercise‐related physiology and performance [12‐14]. However, because analgesics exert a pharmacologic action on key physiological systems related to exercise performance, a theoretical rationale exists whereby these drugs could provide a significant ergogenic effect.…”
Section: Introductionmentioning
confidence: 99%